Spermatogonial Stem Cells: A Review of Essential Factor for Self-Renewal and Differentiation - Silvia W Lestari (Journal of Global Pharma Technology, 2018)
Introduction: Spermatogonial stem cells (SSCs) are considered as promising management for azoospermic patients who couldn’t obtain sperms from the epididymis or directly from testis on assisted reproductive technologies (ART) procedure. The newt highlights of the current research are the emphasis on the utilization of several substances in SSCs culture system which could maintain pluripotency or induce differentiation of SSCs. The objective of this work was to systematically review and discuss articles dealing with the subject of essential factors for self-renewal and differentiation of SSCs. Methods: To this purpose, a computerized search of PubMed database was performed on the general term such as in vitro culture, spermatogonial stem cells, growth factor, hormone and antioxidant. Results: The addition of growth factor, hormone, and antioxidant each play a distinct role in proliferation and differentiation of SSCs. The supplementation of a growth factor activates the cascade of signal transduction toward self-renewal regulation. The addition of hormones such as FSH and testosterone or an antioxidant such as retinoic acid stimulates the differentiation of SSCs in vitro in a certain concentration. Conclusion: The mechanism of these substances in maintaining the pluripotency or inducing cell differentiation varies. Successful development of the SSCs culture system will encourage utilization of SSCs through in vitro proliferation and artificial sperm formation followed by auto-transplantation even though proper investigation is still required prior clinical application.Keywords: Spermatogonial Stem Cell, Growth Factor, Hormone, Antioxidant